Pendidikan Pradīkṣā dalam Lontar Putra Sasana - Sugiharta, I Putu Suweka Oka; Herawan, Kadek Dedy (Sphatika: Jurnal Teologi, 2023)
Sulinggih should be able to become the main teacher for the community, therefore, he must have mature educational experience as well as a good reputation. Hinduism views education as a need for every human being as well as a dimension that is full of purity. When education is far from pure values, it will lose its benefits in forming a generation with noble character. Hinduism holds that education must be given to everyone without exception. However, Sulinggih candidates are required to undergo a more rigorous educational process with denser material. If this is the case, then a prospective sulinggih will automatically have a good reputation and be declared worthy to undergo the purification ritual as a sulinggih.  The further impact is that the quality of education that is born from this process makes all people as educated as possible. The influence of modernism and image worship then led to a reduction in the educational process for Sulinggih candidates. This has led to the emergence of cases of unscrupulous individuals who violate moral norms, religious norms, and even legal norms. In Lontar Putra Sesana, educational methods for Sulinggih candidates have been patterned, which include the dimensions of pedagogy, andragogy, and heutagogy. The aim of this research is to provide a reference for the correct educational pattern of Sulinggih candidates in Hinduism. This research method is of a qualitative type with an accent on library research. The findings of this research state that Lontar Putra Sesana contains the main teachings of pradīkṣā education, which begins at an early age until one is ready to undergo purification as a sulinggih.